2015
DOI: 10.1016/j.foodpol.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Welfare effects of vegetable commercialization: Evidence from smallholder producers in Kenya

Abstract: The CENTER FOR DEVELOPMENT RESEARCH (ZEF) was established in 1995 as an international, interdisciplinary research institute at the University of Bonn. Research and teaching at ZEF addresses political, economic and ecological development problems. ZEF closely cooperates with national and international partners in research and development organizations. For information, see: www.zef.de. ZEF-Discussion Papers on Development Policy are intended to stimulate discussion among researchers, practitioners and policy ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 40 publications
(23 reference statements)
6
56
1
Order By: Relevance
“…The reservation to sell beans reduces with assured alternative income from livestock. The extent of market participation is also positively influenced by the price of beans and is consistent with research conducted on maize in Kenya [30]. Though price alone is not sufficient to stimulate commercialization, it is considered a key incentive for market participation among smallholders [26].…”
Section: Discussionsupporting
confidence: 72%
“…The reservation to sell beans reduces with assured alternative income from livestock. The extent of market participation is also positively influenced by the price of beans and is consistent with research conducted on maize in Kenya [30]. Though price alone is not sufficient to stimulate commercialization, it is considered a key incentive for market participation among smallholders [26].…”
Section: Discussionsupporting
confidence: 72%
“…Commercialization of agriculture is an important means of enhancing crop productivity, food security, and nutrition reduce poverty and incomes (Gebremedhin, Jaleta, & Hoekstra, ; Läpple, Hennessy, & Newman, ; Muriithi & Matz, ; Pingali, ). Carletto, Kilic, and Kirk () present evidence on the long‐term effects of agricultural commercialization on household welfare by using panel data and focus on the nontraditional agricultural export crop in the Central Highlands of Guatemala.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of cash crop vegetable cultivation on smallholder's food security have been widely studied. For example, several authors found that participation in the vegetable business improves farmers' income, food access, availability and consumption [12,13,28,29]. The production of vegetables is found to stimulate exports, the development of rural labour markets and female wage employment in companies.…”
Section: Smallholders Cash Crops and Food Securitymentioning
confidence: 99%
“…Irrigation-led technological changes are the key drivers of productivity growth in the agricultural sector, which in turn has a substantial impact on economic growth. Furthermore, in south Africa and Kenya, linking irrigation with the market orientation has further optimized the benefits of irrigation beyond the smallholders; in addition, access to water security has increased farmers' confidence [28,66]. The literature reveals that irrigation generates an average income of about 323 USD /ha after accounting for the annual investment replacement cost net gross margin from irrigation (60USD/ha) which is more than twice as high as the gross margin from rain-fed agriculture [54].…”
Section: Agriculture Irrigation and Food Security Policies In Ethiopiamentioning
confidence: 99%